Identification and isolation of soluble histones from bovine milk and serum. - Waga, S (1987)
An immunoassay for soluble histones as trace components of biological fluids was developed on the basis of the dual capacity of histones to bind solid-phase DNA and monoclonal anti-histone antibody. Application of this histone-capture assay to bovine milk resulted in a positive signal, and DNA-cellulose chromatography was used to isolate histone-like material in microgram quantities. Western-blot analysis using a panel of anti-histone antibodies demonstrated the presence of histones H2A, H2B and H4 in apparently intact form. DNAase digestion experiments indicated that at least a portion of milk histone was complexed to DNA. Bovine serum was analysed in the same manner on serial DNA-cellulose columns, and H4 and partially degraded H2A were detected by Western-blot analysis. The finding of soluble histones in bovine milk and serum may account for unexpected results when these biological fluids are used as blocking reagents in Western blots and other immunoassays and may have ramifications in the origin and significance of anti-histone antibodies in human disease.